The Problem of ICNIRP (Safety-Guidelines) - Klitzing, Lebrecht (British Journal of Healthcare and Medical Research, 2023)
Worldwide there is an increasing number of healthy problems by electromagnetic field (EMF) exposures, namely produced by wireless telecommunication techniques. But the safety guidelines by ICNIRP (International Commission on Non-Ionizing Radiation Protection) accept only a thermal effect in biosystems, given by a maximal immission of 10 W/m² for these electromagnetic fields. This value was tested by EMF-exposures with the aim of maximal temperature increase of 0,5 K in a dead human body by 6 min exposure (A-Forschungszentrum Seibersdorf). Apart from this thermal effect there are biological reactions by some orders lower compared to the value range stipulated by ICNIRP (Levitt, B.B. and Lai, H., 2010)1.